2002
DOI: 10.1046/j.1432-1033.2002.02902.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐oxygenation of hypoxic simian virus 40 (SV40)‐infected CV1 cells causes distinct changes of SV40 minichromosome‐associated replication proteins

Abstract: Hypoxia interrupts the initiation of simian virus 40 (SV40) replication in vivo at a stage situated before unwinding of the origin region. After re-oxygenation, unwinding followed by a synchronous round of viral replication takes place. To further characterize the hypoxia-induced inhibition of unwinding, we analysed the binding of several replication proteins to the viral minichromosome before and after re-oxygenation. T antigen, the 34-kDa subunit of replication protein A (RPA), topoisomerase I, the 48-kDa su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The nonstructural protein of parvoviruses, such as the NS1 protein of H-1PV and MVM and the large Rep proteins of AAV2, are able to induce a DDR without the presence of viral genomes [10,19,34,68,123], suggesting that they may create damaged cellular DNA though their endonuclease activity. The UV-inactivated AAV2 genome triggered ATR-Chk1 signaling [67,86]. However, during infection of MVM, MVC, B19V and coinfection of AAV2 and adenovirus, the DDR signaling is majorly activated from the DNA replication events [33–35,68], likely due to the specific nicking of viral DNA or generation of viral DNA intermediates that mimic damaged DNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonstructural protein of parvoviruses, such as the NS1 protein of H-1PV and MVM and the large Rep proteins of AAV2, are able to induce a DDR without the presence of viral genomes [10,19,34,68,123], suggesting that they may create damaged cellular DNA though their endonuclease activity. The UV-inactivated AAV2 genome triggered ATR-Chk1 signaling [67,86]. However, during infection of MVM, MVC, B19V and coinfection of AAV2 and adenovirus, the DDR signaling is majorly activated from the DNA replication events [33–35,68], likely due to the specific nicking of viral DNA or generation of viral DNA intermediates that mimic damaged DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The DDR triggered either by expression of the largest nonstructural viral proteins of parvoviruses [10,17,19,123] or by infection with autonomous parvoviruses [33–35] is able to arrest infected cells at S phase or G2/M phase. UV-inactivated AAV2-induced DDR not only arrests cells at G2/M [67], but also triggers apoptosis in tumor cells [86]. Viral infection-induced apoptosis was also observed following DDR activation during MVC infection, which activates the ATM-p53 signaling pathway [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a better model system for chromatin, we have most recently used as a DNA substrate the minichromosomal form of the mammalian virus SV40. The SV40 minichromosome has found frequent use as a model for DNA in cellular chromatin (van Holde 1988, Riedinger et al 2002. It contains a closed-circular double-stranded DNA molecule 5243 bp in length associated with an approximately equal mass of histone proteins (Blasquez et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…before and after triggering initiation, we found that a large number of polypeptides taking part in viral replication were bound to the SV40 minichromosome already under hypoxia. However, the multiprotein complexes necessary for unwinding, primer synthesis and elongation lacked essential components and remained incomplete as long as hypoxia lasted [8]. Reoxygenation triggered fast completion to a functional complex, indicating a specific influence of O 2 ‐dependent cellular changes on critical steps of the assembly of a functional viral replication machinery.…”
mentioning
confidence: 99%